Effects of dolphin-swim activities on the behaviour of an Indo-Pacific bottlenose dolphin population off the south coast of Mozambique. (March 2023) - Rocha, Diana; Marley, Sarah A.; Drakeford, Benjamin; Potts, Jonathan; Gullan, Angie
Abstract: Swim-with-dolphin (SWD) activities are popular but can negatively impact target populations. It is important to consider the behavioural responses of dolphins, and quantify the impact on individuals and populations, as well as maximise opportunities for sustainable tourism that benefits socio-economic growth while encouraging pro-environmental behaviour. This is of relevance in `developing countries, where ecological studies are scarce and tourism industries may have developed before science-based management measures were implemented. This study aimed to determine the effects of SWD tourism on the behaviour of resident Indo-Pacific bottlenose dolphins ( Tursiops aduncus ) in the Ponta do Ouro Partial Marine Reserve (PPMR), Mozambique. Markov-chain models were used to describe dolphin behaviour transition probabilities in different tourism contexts between 2007 and 2009 (low tourism) and 2017–2019 (high tourism). Results detected significant short-term changes in the behaviours of dolphins. In the early years (2007–2009), dolphins were likely to remain in their preceding behaviour if they were resting, travelling, and foraging. However, for later years (2017–2019) this only occurred if they were travelling. Overall, after tourist swims, and under both tourism contexts, dolphins were more likely to travel and less likely to socialise, rest, or forage. The findings raise concerns that, despite current management measures, SWD activities still affect dolphin behaviour and impose short-term negative effects to their activity budget. Our study recommends time- and area-closures, speed restrictions, and mandatory training programmes to all SWD staff. Given that SWD and whale-watching activities take place along the coast of Mozambique, national regulations are urgently needed to minimise potential long-term negative effects on cetacean populations. Highlights: Tourism can negatively affect resident dolphin populations in the short- and long-term. SWD has a significant effect on dolphin behavioural budget. Time and area closures are recommended combined with operator training programmes.